Analysis of Student Perceptions of the Use of ChatGPT as a Learning Media: A Case Study in Higher Education in the Era of AI-Based Education - Adiyono Adiyono; Ali Said Al Matari; Fahmy Ferdian Dalimarta (Journal of Education and Teaching (JET), 2025)
This study aims to identify how students from STIT Ibnu Rusyd Tanah Grogot respond to the use of ChatGPT in the academic world, in the context of the role of artificial intelligence (AI) that can support the learning process in Islamic education. This research utilized a mixed-method design comprising quantitative surveys and qualitative interviews with 120 students to produce comprehensive data. The results of the investigation show how students view ChatGPT as an effective means of increasing the efficiency of certain tasks and significantly improving their understanding of academic material. However, issues were flagged on over-reliance on AI as well as the accuracy of generated information. According to the study, students' attitudes toward ChatGPT are significantly influenced by their level of digital literacy and adherence to Islamic values. Religious values focusing on academic integrity and critical assessment of value and talent, as thoroughly taught in educational institutions contribute to students' shying off from the AI-generated content unless it aligns with Islamic teaching. Qualitative interviews further showed that students view ChatGPT as a tool to support their studies but still desire human supervision to ensure compliance with ethical and religious standards.